1974
DOI: 10.1007/bf01851943
|View full text |Cite
|
Sign up to set email alerts
|

72-Hour perfusion of the isolated spleen at normothermia

Abstract: Summary. A system is described for asanguinous perfusion of isolated spleens at normothermia for 72 hrs. The practicability of this perfusion system is exemplified by the perfusion of pig spleens. The viability parameters were oxygen consumption, lactate/pyruvate quotient, glucose consumption and vascular resistance. The presence of DNA synthesis and phagocytosis by the spleen cells after a 72-hour perfusion were demonstrated. Several human spleens were perfused and it was seen that this system can keep even e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1974
1974
1989
1989

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 10 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…The spleen is one of few tissues on which quantitative information on the fuels of respiration is lacking. There are some data on oxygen and glucose utilization and lactate production in pig spleen perfused with haemoglobin-free perfusates (Pabst & Trepel, 1974). However, these perfusions are likely to be oxygen deficient and this is reflected in a much lower oxygen consumption and higher lactate production than obtained in our studies on rat spleen.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…The spleen is one of few tissues on which quantitative information on the fuels of respiration is lacking. There are some data on oxygen and glucose utilization and lactate production in pig spleen perfused with haemoglobin-free perfusates (Pabst & Trepel, 1974). However, these perfusions are likely to be oxygen deficient and this is reflected in a much lower oxygen consumption and higher lactate production than obtained in our studies on rat spleen.…”
Section: Discussionmentioning
confidence: 47%
“…The perfused spleen has been utilized for investigations in the rat (Ford & Gowans, 1967;Ford, 1969), pig and human (Pabst & Trepel, 1974), where it has been used for the study oflymphocyte migration. However these studies employed heparinized, low haematocrit or erythrocytefree perfusates and revealed little information on spleen metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…The perfusion system, as shown diagrammatically in Figure 1, is comparable to the system previously described (Pabst & Trepel 1974, Reinecke & Pabst 1980 and, therefore, only a brief outline is given. The system consisted of a roller pump, a perfusion chamber, an oxygenator and a regulating system to keep the pH constant.…”
Section: Perfusion Systemmentioning
confidence: 99%